The impact of breast cancer-related lymphedema on rural and small-town Survivors' return-to-work and quality of life: A multiple-case study. (2021) - Anbari, Allison B.; Sun, Yuanlu; McCaffrey, Sarah; Morton, Jamie; Armer, Jane M.
Highlights: Breast cancer survivors living with BCRL in a rural/small town in our study were cognizant of the work/life activities that trigger their BCRL symptoms. Survivors in this study developed self-care routines over time. Our findings suggest there may be rural/small town cultural impacts on the way survivors balance BCRL and quality of life. Abstract: Background: Breast cancer-related lymphedema (BCRL) is a lifelong condition. Millions who develop breast cancer are younger than retirement age and at a lifetime risk for developing BCRL. Rural and small-town survivors may face unique challenges in terms of access to health care and BCRL/survivorship resources. This multiple-case study describes how BCRL influences the work experiences and quality of life (QoL) of survivors living in rural and small towns in Missouri. Methods and Materials: Thirteen survivors from rural and small towns in Missouri completed semi-structured interviews and a standardized QoL instrument. Cases were analyzed using in-vivo and open-coding techniques and constant cross-case comparative methods. Twelve of the 13 participants' data are synthesized into themes to represent an illustrative case. The 13 th case is presented as a contradictory (rival) case. Results: Four themes are represented within the illustrative case – multiple medical encounters; the development of self-care routines; the reciprocity of work/live activities, triggers, and adjustments; and rural/small-town cultural impact. Upon BCRL diagnosis, survivors received intensive treatments, eventually establishing self-care routines. Survivors identified strategies for working around their BCRL when completing work and home responsibilities. The contradictory (rival) case was more recently diagnosed and, as such, had not established self-care and coping mechanisms in the same way. Conclusions and implications: Survivors alleviate BCRL symptoms and improve their QoL by establishing self-care strategies. This provides guidance for client-centered survivorship care-planning and occupational rehabilitation of rural survivors with BCRL. This study provides the foundation for developing information for rural survivors that supports mental preparation and coping skills for BCRL self-management.